Non-Melanoma Skin Cancers and Other Cutaneous Manifestations in Bone Marrow Failure Syndromes and Rare DNA Repair Disorders - Vagher, Jennie; Gammon, Amanda; Kohlmann, Wendy; Jeter, Joanne (Frontiers in Oncology, 2022)
Although most non-melanoma skin cancers are sporadic in origin, these tumors do play a role in several cancer predisposition syndromes. The manifestations of skin cancers in these hereditary populations can include diagnosis at extremely early ages and/or multiple primary cancers, as well as tumors at less common sites. Awareness of baseline skin cancer risks for these individuals is important, particularly in the setting of treatments that may compromise the immune system and further increase risk of cutaneous malignancies. Additionally, diagnosis of these disorders and management of noncutaneous manifestations of these diseases have profound implications for both the patient and their family. This review highlights the current literature on the diagnosis, features, and non-melanoma skin cancer risks associated with lesser-known cancer predisposition syndromes, including bone marrow failure disorders, genomic instability disorders, and base excision repair disorders.